Development of 6G networks and technology - Tripathi, Suman Lata (Wiley, 2025)
This book provides an in-depth exploration of the potential impact of 6G networks on various industries, including healthcare, agriculture, transport, and national security, making it an essential resource for researchers, scholars, and students working in the field of wireless networks and high-speed data processing systems. Development of 6G Networks and Technology explores the benefits and challenges of 5G and beyond that play a key role in the development of the next generation of internet. 6G is targeted to improve download speeds, eliminate latency, reduce congestion on mobile networks, and support advancements in technology. 6G has the potential to transform how the human, physical, and digital worlds interact with each other and the capability to support advancements in technology, such as virtual reality (VR), augmented reality (AR), the metaverse, and artificial intelligence (AI). Machine learning and deep learning modules are also an integral part of almost all automated systems where signal processing is performed at different levels. Signal processing in the form text, image, or video needs large data computational operations at the desired data rate and accuracy. Large data requires more use of IC area with embedded bulk memories that lead to power consumption. Trade-offs between power consumption, delay, and IC area are always a concern of designers and researchers. Energy-efficient, high-speed data processing is required in major areas like biomedicine and healthcare, agriculture, transport, climate change, and national security and defense. This book will provide a foundation and initial inputs for researchers, scholars, and students working in the areas of wireless networks and high-speed data processing systems. It also provides techniques, tools, and methodologies to develop next-generation internet and 6G.
Keywords: Elektronik, Elektrotechnik, Nachrichtentechnik; Aufsatzsammlung